2022
DOI: 10.3390/jof8030244
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenes Specially Produced by Fungi: Structures, Biological Activities, and Biosynthesis (2010–2020)

Abstract: Fungi have traditionally been a very rewarding source of biologically active natural products, while diterpenoids from fungi, such as the cyathane-type diterpenoids from Cyathus and Hericium sp., the fusicoccane-type diterpenoids from Fusicoccum and Alternaria sp., the guanacastane-type diterpenoids from Coprinus and Cercospora sp., and the harziene-type diterpenoids from Trichoderma sp., often represent unique carbon skeletons as well as diverse biological functions. The abundances of novel skeletons, biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 208 publications
(293 reference statements)
0
14
0
Order By: Relevance
“…Here, the effects of an ELF extract and isolated secondary metabolites on immune checkpoints in non-small lung cancer cells were investigated. This study identified (Figure 7 Radianspenes C and D, and dahliane D, are secondary metabolites (diterpenoids) found in fungi (Zhang and Feng, 2022). A previous study showed that radianspene C from Coprinus radians showed cytotoxic effect on MDA-MB-435 human breast cancer cells with an IC 50 value of 0.91 μM (Ou et al, 2012).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Here, the effects of an ELF extract and isolated secondary metabolites on immune checkpoints in non-small lung cancer cells were investigated. This study identified (Figure 7 Radianspenes C and D, and dahliane D, are secondary metabolites (diterpenoids) found in fungi (Zhang and Feng, 2022). A previous study showed that radianspene C from Coprinus radians showed cytotoxic effect on MDA-MB-435 human breast cancer cells with an IC 50 value of 0.91 μM (Ou et al, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…Radianspenes C and D, and dahliane D, are secondary metabolites (diterpenoids) found in fungi ( Zhang and Feng, 2022 ). A previous study showed that radianspene C from Coprinus radians showed cytotoxic effect on MDA-MB-435 human breast cancer cells with an IC 50 value of 0.91 μM ( Ou et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally, they have mainly cyclic carbon skeleton especially tri‐ and tetracyclic ring systems. [ 79 ] The main carbon skeletons and their transformation between each other have been shown in Figure 12. Importantly, compounds of this family show diverse biological activities, including anti‐tumor, anti‐renal fibrosis, antimicrobial, and neurotrophic effects.…”
Section: Diterpenoidsmentioning
confidence: 99%
“…Diterpenoids, derived from the universal precursor geranylgeranyl diphosphate (GGPP), are a diverse class of structurally complex and biologically important natural products mainly produced by plants, fungi, bacteria, and marine invertebrates. Their structural complexity and diversity are mainly generated by diterpene synthases (DTSs), which can synthesize cyclic molecules with multiple stereogenic centers from the acyclic precursor GGPP in a single reaction. Thus, numerous DTSs have been identified and characterized to understand the basis for the production of such diverse molecular architectures. The main classes of DTSs were described as class I and II terpene synthases, depending on the reaction mechanisms and amino acid sequences.…”
mentioning
confidence: 99%